A Short Handbook for writing essays in the Humanities and Social Sciences - Allosso, Salvatore; Allosso, Dan; Open Textbook Library (Open Textbook Library, 2019)
A retired master teacher of English and Comparative Literature teams up with his son, a History professor, on a new version of the writing manual he wrote and used for decades at the University of California, Davis.
1. Analyzing Texts, Taking Notes -- 2. Discovering a Topic, Preparing for Discussion -- 3. Creating a Thesis -- 4. Ordering Evidence, Building an Argument -- 5. Coherent Paragraphs -- 6. Effective Sentences -- 7. Appropriate Words -- 8. Revising -- 9. Revision Checklist
In English.
Description based on print resource
Keywords: Academic achievement -- Textbooks